Flowering response of torch ginger (Etlingera elatior) to PK fertilization - RAMDAN HIDAYAT; PANGESTI NUGRAHANI; RAHMATUN NISFUL MAGHFIROH (Society for Indonesian Biodiversity, 2025)
Abstract. Hidayat R, Nugrahani P, Maghfiroh RN. 2025. Flowering response of torch ginger (Etlingera elatior) to PK fertilization. Biodiversitas 26: 6305-6315. Demand for the flowers of Etlingera elatior has increased, but predictable and timely flowering is constrained by its naturally long vegetative phase. This research aimed to determine the combined effect of dosage and frequency of PK compound fertilizer in inducing flowering in torch ginger. The field trial was carried out at Dapoer Ketjombrang Garden, Giripurno Village, Bumiaji District, Batu City, East Java, Indonesia, from December 2023 to April 2024. A factorial experiment was conducted using a randomized complete block design (two factors: dosage (D): 50, 100, 150, 200 g/clump; frequency (F): 1, 2, 3 applications at 30, 30+45, and 30+45+60 DAT, respectively) with three replicates (36 plots, 3 plants/plot, total 108 plants) was used. Data were analyzed using a two-way ANOVA (dosage, frequency, dosage×frequency), and means were compared using Tukey’s HSD (α: 0.05). The combination D4F2 (200 g, 2x at 30 and 45 DAT) produced the earliest flowering (mean 21.89 DAT). The dosage D3 (150 g) produced the best vegetative growth and, when combined with F2, gave the highest number of flowers (23.78 flowers/clump). Dosage effects were significant (p<0.05) for several traits; frequency had limited main effects, but dosage×frequency interactions were observed. The highest C:N ratio, antioxidant level, and vitamin C were observed at D4; regression between C:N and flowering age showed R²: 0.92 (p: 0.041). Overall, applying 150-200 g PK fertilizer per clump in two applications (30 and 45 DAT) provides an effective strategy to induce earlier flowering and increase flower productivity under the conditions tested. Multi-season and multi-site validation is recommended before making broad recommendations.